Control strategies for the More Electric Aircraft starter-generator electrical power system - Yeoh, Seang Shen (2016)
The trend towards development of More Electric Aircraft (MEA) has been driven by increased fuel fossil prices and stricter environmental policies. This is supported by breakthroughs in power electronic systems and electrical machines. The application of MEA is expected to reduce the aircraft mass and drag, thereby increasing fuel efficiency and reduced environmental impact. The starter-generator (S/G) scheme is one of the solutions from the MEA concept that brings the most significant improvement to the electrical power generation system. A S/G system is proposed from the possible solutions brought by the MEA concept in the area of electrical power generation and distribution. Due to the wide operating speed range, limited controller stability may be present. This thesis contributes to the control plant analysis and controller design of this MEA S/G system. The general control requirements are outlined based on the S/G system operation and the control structure is presented. The control plants are derived specifically to design the controllers for the S/G control scheme. Detailed small signal analysis is performed on the derived plant while taking into consideration the aircraft operating speed and load range. A safe range for the controller gains can then be determined to ensure stable operation throughout the S/G operation. Adaptive gain and a novel current limit modifier are proposed which improves the controller stability during S/G operation. Model predictive control is considered as an alternative control strategy for potential control performance improvements with the S/G system. The technical results and simulations are supported by Matlab®/Simulink® based models and validated by experimental work on a small scaled drive system.